2018
DOI: 10.1155/2018/4843985
|View full text |Cite
|
Sign up to set email alerts
|

Action Observation Treatment Improves Upper Limb Motor Functions in Children with Cerebral Palsy: A Combined Clinical and Brain Imaging Study

Abstract: The aim of the present study was to assess the role of action observation treatment (AOT) in the rehabilitation of upper limb motor functions in children with cerebral palsy. We carried out a two-group, parallel randomized controlled trial. Eighteen children (aged 5–11 yr) entered the study: 11 were treated children, and 7 served as controls. Outcome measures were scores on two functional scales: Melbourne Assessment of Unilateral Upper Limb Function Scale (MUUL) and the Assisting Hand Assessment (AHA). We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
106
0
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 35 publications
3
106
0
18
Order By: Relevance
“…The same pattern emerges for MUUL scores, where improvements of the quality of upper limb motor functions were induced only by AOT, but not by VOT. These results extend those obtained in previous research (Buccino et al, , ; Sgandurra et al, ). Indeed, MUUL results showed specific functional gain following the intervention, and also met the requirements for an authentic clinical improvement.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The same pattern emerges for MUUL scores, where improvements of the quality of upper limb motor functions were induced only by AOT, but not by VOT. These results extend those obtained in previous research (Buccino et al, , ; Sgandurra et al, ). Indeed, MUUL results showed specific functional gain following the intervention, and also met the requirements for an authentic clinical improvement.…”
Section: Discussionsupporting
confidence: 93%
“…Since µ rhythm suppression is related to the activation of the mirror system during observation and performance of goal‐directed actions, the AOT‐induced increase in µ rhythm suppression over C3/C4 can be ascribed to the improved activation of motor areas. This result is in line with findings from fMRI studies in both children with CP (Buccino et al, ) and adult stroke patients (Ertelt et al, ) showing the increased activation of frontal and parietal areas (in particular of the premotor cortex and the superior temporal gyrus) following AOT. Interestingly, despite no significant difference was found between sensorimotor activation recorded over Cz between pre‐ and post‐AOT, we reported a significant absolute activation (i.e., compared to baseline) over Cz at post‐treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors concluded that children exploit the mirror mechanism to represent the action goal rather than its kinematics. A recent randomized controlled trial investigating the clinical and brain activity changes induced by AOT in children with CP was able to both confirm the clinical efficacy of AOT on hand motor function, and to show that children treated with AOT had stronger activation in a parieto‐premotor circuit for hand‐object interaction, supporting the notion that AOT is able to shape sensory‐motor brain circuits improving the impaired function.…”
mentioning
confidence: 82%